Overcoming challenges in Ethiopia’s nutrition governance - Ayele, Seife; Nisbett, Nicholas; Zegeye, Elias Asfaw (Institute of Development Studies, 2020)
Reducing undernutrition is crucial for Ethiopia’s development. Ethiopia has implemented multi-sectoral nutrition programmes for over a decade, with some success. However, challenges remain in coordination and implementation of these programmes. Based on an in-depth study of the political economy challenges facing the country’s nutrition governance structure, this policy briefing explores why nutrition governance has been ineffective. It makes recommendations for governance improvements that will accelerate Ethiopia’s reduction in undernutrition, including the establishment of an independent and well-equipped nutrition governance agency.